Influence of Dy doping on the structural, vibrational, optical, electronic, and magnetic properties of SnO2 nanoparticles - Aquino J.C.R. (2020)
Dysprosium (Dy3+)-doped tin oxide (SnO2) nanoparticles (NPs) have been successfully synthesized using the chemical polymer precursor method. This material blends the holding matrix’s electronic properties with dysprosium’s optical and magnetic properties, making it a promising material for technological applications. X-ray diffraction patterns and the Raman spectra of all NPs indicated the formation of only the SnO2 phase. The decrease in particle size (from ~ 11 to ~ 6 nm) and increase in lattice parameters depending on the Dy content were determined. The latter proves the solid solution between Sn and Dy ions, which is in agreement with the ionic radii mismatch between them. Transmission electron microscopy (TEM) confirms the particle size and size reduction observed through XRD. X-ray photoelectron spectroscopy (XPS) results suggest a change of the oxidation state from Sn4+ to Sn2+with the Dy content, with more Dy3+ than the values accessed from EDS analysis. The latter strongly suggests that the Dy3+ surface gets enriched as the dopant amount increases, driving to the surface passivation of structural defects in good agreement with Raman spectroscopy results. Optical properties show a modest bandgap reduction with the Dy content. Meanwhile, magnetic measurements indicate the coexistence of ferromagnetic and paramagnetic contributions for 1% Dy-doped SnO2 NPs. However, only the paramagnetic contribution is observed after this concentration level. The ferromagnetic contribution detected for lower dopant amounts (? 1%) has been attributed to the presence of bound magnetic polarons (BMP’s). Graphical abstract: [Figure not available: see fulltext.] © 2021, The Author(s), under exclusive licence to Springer Nature B.V.